Paphlagonia Hadrianoupolis’i Geç Roma Villası’nda Yer Alan Duvar Resimlerinin Korunması Kapsamında Ön İnceleme Çalışmaları. - Yetiş, Ezgin; Eroğlu, Murat; Deniz, Kıymet; Kadıoğlu, Yusuf Kağan (Electronic Turkish Studies, 2021)
It consists of preliminary studies carried out the wall paintings found in the Late Roman Villa, Karabük Hadrianoupolis Ancient City. In the examination studies; the conservation status of the paintings, past restorations, humidity conditions, UV-light examinations, optical microscope images and analytical measurements of the samples taken from the paint and renders were evaluated. Then some suggestions were given about the conservation processes. There are wall paintings in the room of 3, 4 and 5 in the villa. Merely the protection cover of room-3 was removed and samples were taken. Thin-section petrography, crosssection optical microscope images, FTIR (Fourier Transform Infrared) Spectroscopy, XRF (X-Ray Fluorescence), XRD (X-ray diffraction) and CRS (Confical Raman Spectroscopy) were examined. Lime, sulfate salts and acrylic resins were determined in IR spectrum and acrilic resins may be used in past restorations. Mortars with medium hydraulic and natural cement renders/mortars in XRF, calcite crystal structures in XRD; pigments based on carbon and siderite (FeCO3) in CRS were identified. Broken bricks (cocciopesto) and natural fibres mortars are observed in thin-section petrography. Moreover, the images in cross-section optical microscope examinations indicate fresco techniques. In the 5-day preliminary study, which started with the removal of the protective cover of the wall paintings and completed with a new cover, the moisture changes of the plaster was determined and 80% relative humidity were measured. Humidity control was ensured and past retouching/overpaintings was tried to be determined with UV-light. Within the framework of analytical studies and observations, conservation suggestions were presented such as drainage and temporarily roof covering on wall paintings, cleaning process of the fresco painting technique, removing the white layer based on limestone and preventing the plant growth.